Andragogic principles in case-based discussion among medical interns in a tertiary hospital - Quino, Raquel Joaquin-; Melflor A. Atienza, MD MHPED (Manila National Teacher Training Center for the Health Professions, 2020)
Andragogy or the theory of adult learning is relevant to medical education, especially in the clinical internship learning context. This setting focuses on the students, the faculty, and patients interacting together while developing competencies as future practitioners. Medical interns are active adult learners, enhancing their development of knowledge, skills, and positive attitudes, and pursuing professionalism. Within the internship context, students and faculty, as well as other post-graduate trainees like residents and fellows engage in a series of case-based discussions (CBDs). This study seeks to identify the basic principles of andragogy while medical interns participate in CBDs. The study also determines selected demographic factors associated with the andragogic principles. Respondents included 80 interns selected by convenience sampling when they rotated at the Department of Ophthalmology and Visual Sciences in a tertiary referral hospital. The study used a combination of descriptive quantitative and qualitative research design. A valid instrument using the Adult Learning Principles Design Elements Questionnaire (ALPDEQ) was used to measure the medical intern's andragogic orientation. ALPDEQ consists of 28 items and rated using a 5-point scale where 1: Strongly Disagree, 2: Disagree, 3: Neither Agree nor Disagree, 4: Agree, and 5: Strongly Agree. A direct, non-participant observation of case- based discussions, conducted at the department was also conducted by the researcher and research associate. The occurrence of andragogic principles specifically motivation, experience, need to know, readiness and self-directedness were observed during the conduct of case-based discussion xi among medical interns. The scores obtained by direct observation by the researcher and research assistant were compared through Kappa analysis. Moderate agreement was observed in the principle of experience with a kappa = 0.55. This was followed by the principle of self- directedness with 0.36 showing fair agreement. The two raters showed slight agreement in the principles of motivation and need to know with Kappa = 0.07 and 0.05 respectively. Poor agreement was seen in the principle of readiness at kappa = -0.22. Interns? ALPDEQ mean ratings were 4.60 for motivation (sd=0.42), 4.55 for experience (sd=0.48), 4.59 for need to know (sd=0.40), 4.44 for readiness (sd=0.50), 4.60 for self- directedness (sd=0.44), and 4.79 for end-of-rotation (sd=0.34). There was no association between principles of andragogy, and demographic factors such as age, gender, civil status, medical school, preparatory medical course and place of origin. The study proved that CBDs provide medical interns adequate venues to be self-directed and apply the principles of andragogy. CBDs are effective strategies where interns work in teams, search for knowledge, in a workplace-based setting. Further studies exploring CBDs with consultants and other departments will help facilitate improvement in the internship program and enhance additional educational outcomes in the field of adult learning in medicine and health professions education as a whole.
Thesis
Panel Members: Melflor A. Atienza, MD, MHPEd, Chair/Adviser. Erlyn A. Sana, PhD, Reader/Critic. Members: Maria Lourdes Dorothy S. Salvacion, DDM, MHPED, Teresita R. Castillo, MD, MHPEd, Patricia M. Khu, MD, MSc
Keywords: Andragogy; Case-based discussion; Self-directed learning; Medical interns